Effect of Momordica charantia L. supplementation on patients with Diabetes mellitus: A systematic review (Research, Society and Development, 2021)
Diabetes mellitus (DM) is a chronic, multifactorial disease that comprises a heterogeneous group of metabolic disorders, being classified as a public health problem that is difficult to control. The use of medicinal plants in disease control has been gaining a lot of visibility due to therapy, easy access and successful clinical cases. Some plant species are used to suppress symptoms caused by diabetes mellitus in association or not with traditional medicine, among them, the São Caetano melón (Momordica charantia L.). The current review aimed to analyze the main researches on the use of Momordica charantia L. in the treatment of diabetes mellitus. This is a systematic review based on original articles published in English that were selected from the databases Pubmed, Cochrane Library, LILACS and ScienceDirect. After applying the inclusion and exclusion criteria, a total of 07 articles were finally selected for the research, where it was observed that M. charantia L. proved to be an alternative with a potential antidiabetic effect in the control of diabetes mellitus.